Energy Harvesting in Wireless Sensor Networks and Internet of Things. - Shaikh, Faisal Karim; Zeadally, Sherali (Control, Robotics and Sensors Ser., 2022)
The energy efficiency paradigm is a major bottleneck for the development of wireless sensor networks (WSNs) and Internet of Things (IoT) architectures and technologies. This edited book presents comprehensive coverage of energy harvesting sources and techniques that can be used for WSN and IoT systems.